Efecto de la aplicación de cuatro biofertilizantes a base de Azospirillum brasilense sobre el rendimiento de grano en el cultivo de maíz, en la zona de Babahoyo - Cruz Vera, José Gabriel (2015)
The trial was held in the grounds of the Farm Palmar, belonging to the Faculty of Agricultural Sciences, Technical University of Babahoyo in the hybrid corns 'Iniap 601' and 'Dekalb 7088', in order to assess the effects of fertilizers on agronomic characteristics; identify the best dose and biofertilizer order to maximize grain yield; and economically analyze the treatments according to the production cost and performance. The treatments were hybrids 'Dekalb 7088' and 'Iniap 601'; subtreatments Noctin Azo at doses of 300 and 400 g/ha; Azostic at doses of 400 and 500 g/ha; Nitragin in doses of 240 and 360 cc/ha; Micro Asp in doses of 500 and 600 cc/ha. In addition, an unfertilized and fertilized without biofertilizer witness was included; giving a total of ten treatments. Experimental design "split plots" was used in three repetitions; where the main plots corresponded to the treatments and subtratamientos as experimental subplots. The experimental subplot consisted of 4 rows spaced 6m length 0.70 m giving an area of 16.8 m2; while the useful area consisted of the two central rows being an area of 8.4 m2.......